Short-time kinetics and initial correlations in nonideal quantum systems - Kremp, D.; Semkat, D.; Bornath, Th. (Condensed Matter Physics, 2006)
There are many reasons to consider quantum kinetic equations describing the evolution of a many-particle system on ultrashort time scales, e. g. correct energy conservation in nonideal plasmas, buildup of correlations (bound states), and kinetics of ultrafast processes in short-pulse laser plasmas. We present a quantum kinetic theory including initial correlations and being valid on arbitrary time scales. Various examples of short-time relaxation processes, such as relaxation of the distribution function and the energy, are shown. Furthermore, gradient expansions of the general equations and the role of bound states are discussed.